Safety of Low-Molecular-Weight Heparin in Pregnancy: A Systematic Review - Sanson, Bernd-Jan; Lensing, Anthonie W. A.; Prins, Martin H.; Ginsberg, Jeffrey S.; Barkagan, Zinoviy S.; Lavenne-Pardonge, Edith; Brenner, Benjamin; Dulitzky, Mordechay; Nielsen, Jørn D.; Boda, Zoltan; Turi, Susanna; Mac Gillavry, Melvin R.; Hamulyák, Karly; Theunissen, Ingrid M.; Hunt, Beverley J.; Büller, Harry R. (Thrombosis and Haemostasis, 1999)
Unfractionated heparin (UFH) remains the anticoagulant of choice during pregnancy. Low-molecular-weight heparins (LMWH) are an attractive alternative to UFH due to their logistic advantages and their association with a lower incidence of osteoporosis and HIT. We reviewed all published clinical reports concerning the use of LMWH during pregnancy. In addition, participants of an international interest group contributed a cohort of pregnant women treated with LMWH. Pregnancies were divided into two groups; those with and those without maternal comorbid conditions. The number of adverse fetal outcomes and the occurrence of maternal complications were evaluated in the two groups. In the group of women with comorbid conditions (n = 290), 13.4% of the pregnancies were associated with an adverse fetal outcome. In contrast, in the group of women without comorbid conditions (n = 196), 3.1% were associated with an adverse outcome, which is comparable to that seen in the normal population. We conclude that LMWH appear to be a safe alternative to unfractionated heparin as an anticoagulant during pregnancy.